Analysis of Islamic Business Ethics in Digital Business Practice - Rangga Salam; Yurmaini Yurmaini; Dewi Sundari; Salman Nasution (Yayasan Rahmat Islamiyah, 2026)
This study aims to find the limits that are allowed and prohibited according to the principles of Islamic business ethics in running a business through the digital economy. This study uses a qualitative research method based on library research. The results of this study are the analysis of Islamic business ethics in digital business practices showing that the application of sharia principles such as honesty, justice, trustworthiness, and responsibility are the main keys to creating halal, blessed, and sustainable transactions.